2022
DOI: 10.1186/s12891-022-05350-5
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency electrical stimulation alleviates immobilization-evoked disuse muscle atrophy by repressing autophagy in skeletal muscle of rabbits

Abstract: Background The study aimed to investigate the effect of low-frequency electrical stimulation (LFES) on disuse muscle atrophy and its mechanism in a rabbit model of knee extension contracture. Methods This study involved two experiments. In the time-point experiment, 24 rabbits were randomly divided into 4 groups: Control 1 (Ctrl1 group), immobilization for 2 weeks (I-2 group), immobilization for 4 weeks (I-4 group), and immobilization for 6 weeks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…In order to observe the natural process of joint contracture, we established an animal model using immobilization by aluminum plates. Joint contracture is characterized by a reduction of joint range of motion compared with normal joints [ 34 , 35 ], thus decreased join range of motion represents increased degree of joint contracture. Previous studies have suggested that joint contracture occur within 1 week of knee joint immobilization and progress in a time-dependent manner [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to observe the natural process of joint contracture, we established an animal model using immobilization by aluminum plates. Joint contracture is characterized by a reduction of joint range of motion compared with normal joints [ 34 , 35 ], thus decreased join range of motion represents increased degree of joint contracture. Previous studies have suggested that joint contracture occur within 1 week of knee joint immobilization and progress in a time-dependent manner [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parkin-mediated mitophagy is one of the most important mitophagy pathways, and COXIV is a well-known mitophagy marker protein 25 . Previous studies suggested that protein levels of LC3B-II increased after IM, and electrical stimulation can inhibit the overexpression of LC3B-II 19 . In this study, the activation of mitophagy on the muscles after IM could be detected by examining the upregulation of Parkin and the down-regulation of COXIV.…”
Section: Discussionmentioning
confidence: 87%
“…25 Previous studies suggested that protein levels of LC3B-II increased after IM, and electrical stimulation can inhibit the overexpression of LC3B-II. 19 In this study, the activation of mitophagy on the muscles after IM could be detected by examining the upregulation of Parkin and the down-regulation of COXIV. Moreover, the expression of Parkin reached the highest level and the expression of COXIV reached the lowest level at 2 wks after IM, which indicated that Parkin-mediated mitophagy attained to the highest level at 2 wks after IM.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations